Advancing Multi-Energy Marine Platforms: Insights from the TwinPower Project on Digital Twins, Renewable Technologies, and Coastal Integration (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The TwinPower project is focused on the development and testing of multi-energy marine platforms, marine spatial planning, environmental impact assessments, and dissemination strategies, through the project ENEPORTS initiative, which aims to disseminate the prototype through the digital twin.The platform uses a multi-energy approach by combining wave, tidal, wind, and photovoltaic technologies. Solar energy contributes significantly to the platform's power supply, with a peak output of 1170 W under optimal weather conditions.  This platform also allows space for tidal and wind turbines for versatility, but with optimized Blade Element Momentum models that allow efficiency in energy conversion.Piezoelectric cells are being tested for wave energy harvesting. The goal is to ensure the suitability of these cells for powering independent, battery-free IoT systems. Initial results show a production of up to 50 J (or Ws) with 0.25 m² during one hour of rough seas. This energy could power a microcontroller around one minute, every hour under turbulent wave conditions. This IoT system could independently monitor the environmental and operational behavior. Preliminary testing showed several advantages and limitations of using piezoelectric technology in practice, demonstrating the potential to supply lightweight monitoring systems.The platform also incorporates two mechanical tensioners, originally designed for mooring applications, which have been adapted to capture wave energy. Adaptation is currently under development and includes an integrated generator for power production between 100 W and 1 kW, depending on the sea state.Replicability is one of the core goals, focusing on the use of data from the pilot site for digital modeling. Field tests at Honfleur validate the numerical model feasibility for adaptation to chosen geographic sites, enabling exportable solutions via the validated platform. Challenges remain, however, regarding the mechanical couplings and structural constraints presented by the central pile anchoring system.The digital twin of the project is developed through multi-physics simulations using Matlab Simulink. This digital twin integrates data from real-time environmental monitoring systems. Current achievements include accurate modeling for solar irradiance, wind patterns, tidal currents, and turbine efficiencies, while refinement is ongoing for wave dynamics and piezoelectric performance.The central pile anchoring system is a first prototype allowing several energy resources but also introduces some limitations. These systems ensure structural stability and further integration of various energy harvesting technologies while being easier to install. These may also impose possible problems with hydrodynamic drag and mechanical stress distribution within the platform. Advantages include increased resource harvesting potential and higher modular adaptability, whereas the disadvantages underline the need for further optimization in mechanisms of energy transfer and long-term durability.International conferences such as AWTEC 2024 and EURONAVAL 2024 have been attended, along with active collaboration with the project ENEPORTS partners, to fast-track the adoption of similar platforms in other coastal areas. The potential integration into broader initiatives promises considerable contributions toward the development of sustainable marine energy and energy transition goals.Future work will look at scalability in TwinPower, including improvements to mechanical tensioner systems, advancements in piezoelectric energy harvesting, and refinements in the accuracy of digital twins.